2011
DOI: 10.1111/j.1748-720x.2011.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Racial and Ethnic Minorities in Genetic Research: Advance the Spirit by Changing the Rules?

Abstract: Genetic research aimed at understanding human health and disease is grounded in the study of genetic variation. The inclusion of research subjects with diverse ancestral backgrounds is essential for genetic and genomic research that fully explores human diversity. Large‐scale cohort studies and biobanks in Europe and the United States often do not include the breadth of ethnic and racial diversity observed in their countries' citizens. This article explores the findings of a qualitative study of U.S. scientist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
1
27
1
Order By: Relevance
“…According to the American Association of Colleges of Nursing (2015), only 13% of nursing faculty nationwide identify as African American, Latino or another underrepresented minority group, while these groups made up 37% of the U.S. population in 2012 and are expected to grow to over 50% by 2043 (United States Census Bureau, 2014). The exclusion of minority communities from genomic studies may be due, in part, to researchers’ discomfort in dealing with issues of race and other barriers to recruiting minority populations (Knerr, Wayman, & Bonham, 2011). These barriers could result in genomic studies with insufficient samples among minority groups and, ultimately, the discarding of those groups from analyses.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American Association of Colleges of Nursing (2015), only 13% of nursing faculty nationwide identify as African American, Latino or another underrepresented minority group, while these groups made up 37% of the U.S. population in 2012 and are expected to grow to over 50% by 2043 (United States Census Bureau, 2014). The exclusion of minority communities from genomic studies may be due, in part, to researchers’ discomfort in dealing with issues of race and other barriers to recruiting minority populations (Knerr, Wayman, & Bonham, 2011). These barriers could result in genomic studies with insufficient samples among minority groups and, ultimately, the discarding of those groups from analyses.…”
Section: Discussionmentioning
confidence: 99%
“…17 Researchers often default to social labels of race and ethnicity to describe research participants, but geneticists acknowledge that classification as observed and self-reported race are imprecise proxies for clustering individuals. 18 Findings from one recent large-scale genetic ancestry study illustrate that more than six million Americans who self-identify as European likely carry African ancestry. 19 Mixed ancestry is ubiquitous around the world, and most individuals have multiple genetic ancestry markers that are not captured well by racial and ethnic categories.…”
Section: Study Design Populations and Biasmentioning
confidence: 99%
“…; Geller, Adams, and Carnes ; Geller et al. ; Knerr, Wayman, and Bonham ) and by extension, has not encouraged researchers to shift toward a more critical understanding of how race shapes disease susceptibility. The investigator's paradox, it seems, reflects the larger issue of how to think about and utilize race and human variation as meaningful categories in biomedical research.…”
Section: Race In the Context Of Social Science And Biomedicinementioning
confidence: 99%
“…This federal mandate, while attempting to uphold ethical tenets, can hinder the ability to think about or value human difference in innovative and meaningful ways. Furthermore, according to several meta-analyses, the mandate has not mitigated the lack of minority representation in research (Chen et al 2014;Geller, Adams, and Carnes 2006;Geller et al 2011;Knerr, Wayman, and Bonham 2011) and by extension, has not encouraged researchers to shift toward a more critical understanding of how race shapes disease susceptibility. The investigator's paradox, it seems, reflects the larger issue of how to think about and utilize race and human variation as meaningful categories in biomedical research.…”
mentioning
confidence: 99%